2012
DOI: 10.9734/bjmmr/2012/944
|View full text |Cite
|
Sign up to set email alerts
|

High Membrane Cholesterol in CLL B-Cells and Differential Expression of Cholesterol Synthesis Genes in IG GENE-Unmutated vs Mutated Cells

Abstract: Objectives: Chronic lymphocytic leukaemia (CLL) is associated with abnormalities of the B-Cell Receptor (BCR) signalling, including low responsiveness to antigenic stimulation and constitutive phosphorylation of several components of the signalling pathway. In Bcells, BCR-mediated signalling is regulated in part by the amount of membrane cholesterol. It was observed that Statins, pharmacological inhibitors of cholesterol synthesis, induce apoptosis of CLL cells in vitro and in vivo. Having previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has been found that statins (Lovostatin), pharmacological inhibitors of cholesterol synthesis, induce apoptosis of CLL cells in vitro and in vivo. In addition, ectopic expression of CD5 in B-cell line stimulates the transcription of genes involved in cholesterol synthesis [5]. B lymphocytes express a variety of specific surface antigens which can be targets for the chimeric antigen receptor (CAR) that destroy leukemia cells [ Figure 3].…”
Section: Previous International Researchermentioning
confidence: 99%
“…It has been found that statins (Lovostatin), pharmacological inhibitors of cholesterol synthesis, induce apoptosis of CLL cells in vitro and in vivo. In addition, ectopic expression of CD5 in B-cell line stimulates the transcription of genes involved in cholesterol synthesis [5]. B lymphocytes express a variety of specific surface antigens which can be targets for the chimeric antigen receptor (CAR) that destroy leukemia cells [ Figure 3].…”
Section: Previous International Researchermentioning
confidence: 99%
“…It has been found that statins (Lovostatin), pharmacological inhibitors of cholesterol synthesis, induce apoptosis of CLL cells in vitro and in vivo. In addition, ectopic expression of CD5 in B-cell line stimulates the transcription of genes involved in cholesterol synthesis [5].…”
mentioning
confidence: 99%